Amplatzer vascular plug for alternate treatment in pelvic congestive syndrome in Dr. Soetomo General Hospital: A case report - Raharjo, Fumansha Cipto; Danang Himawan Limanto (Indonesian Vascular Access Association (IVAA), 2024)
Introduction: One of the common causes of chronic pelvic pain in reproductive-age women is pelvic congestion syndrome (PCS). This pain can be constant or intermittent for 3-6 months, occurring throughout the menstrual cycle, arising in the abdominal or pelvic area, and is not related to pregnancy. Complaints of chronic pelvic pain are as much as 10-20% of gynecological consultations, and only 40% of them are referred to specialists for evaluation. 10 – 60 % of PCS is caused by insufficient iliac vein, ovarica vein, or both. Incompetent ovarian vein ligation can head to a favorable result. An endovascular technique using an embolization coil, glue, foam, or amplatzer can be an alternative treatment for PCS. Case Description : Women 50 years old whom a history of chronic pelvic pain, CT angiography showed Left ovarica vein dilatate and prominant. Durante operation, approach from a right femoral vein with a catheter to the left renal and ovarian veins. Amplatzer vascular plug was deployed at the left ovarian vein and evaluated. There wasn’t insufficient. The Patient was discharged the day after the operation. Conclusion : In conclusion, venous occlusion with vascular plug for PCS management is safe and effective with an embolization agent or surgery with a significant enhancement in pelvic symptoms for PCS.